Simulation of Cone Beam Computed Tomography of Core Samples from Oil and Gas Taking into Account Spectral Information in Geant4; Radiation from Relativistic Electrons in Periodic Structures (RREPS-19) - Filatov N. A. Nikolay Alexandrovich; Gogolev A. S. Aleksey Sergeevich; Chistyakov S. G. Sergey Gennadevich; Vukolov A. V. Artem Vladimirovich (Applications of Monochromatic X-ray, [gamma]-ray, 2019)
Title screen